Investigation of the biological and anti-cancer properties of ellagic acid-encapsulated nano-sized metalla-cages - Dubey A (Dove Medical Press, 2015)
Abhishek Dubey,1,* Dae Won Park,2,* Jung Eun Kwon,2 Yong Joon Jeong,2 Taegeun Kim,1 Inhye Kim,3 Se Chan Kang,2 Ki-Whan Chi1 1Department of Chemistry, University of Ulsan, Ulsan, 2Department of Life Science, Gachon University, Seongnam, 3Laboratory of Bio-Resources, Yongin-si, Gyeonggi-Do, Republic of Korea *These authors contributed equally to this work Abstract: Three new large hexanuclear metalla-prisms 9–11 incorporating 1,3,5-tris(pyridin-4-ylethynyl)benzene (tpeb) 4 and one of the dinuclear arene ruthenium clips [Ru2(p-iPrC6H4Me)2(OO∩OO)][CF3SO3]2 (OO∩OO =2,5-dioxydo-1,4-benzoquinonato [dobq] 1, 5,8-dihydroxy-1,4-naphthaquinonato (donq) 2, and 6,11-dihydroxy-5,12-naphthacenedionato [dotq] 3), which encapsulate the guest molecule ellagic acid (2,3,7,8-tetrahydroxy-chromeno[5,4,3-cde]chromene-5,10-dione, 5) were prepared. All complexes were isolated as triflate salts in good yields and were fully characterized by 1H NMR spectroscopy and electrospray ionization mass spectrometry. The photophysical properties of these metalla-prisms were also investigated. Compounds 9 and 10 showed potent antioxidant activity, but 10 had the superior ORACPE value (1.30±0.020). Ellagic acid (5) and compound 11 showed weaker activity than that of Trolox. The 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay showed that the metalla-prism compounds exhibit anticancer properties in vitro. Compound 10 inhibited the growth of all cancer cell lines at micromolar concentrations, with the highest cytotoxicity observed against A549 human lung cancer cells (IC50 =25.9 µM). However, these compounds had a lower anti-cancer activity than that of doxorubicin. In a tumoricidal assay, ellagic acid (5) and compound 10 induced cytotoxicity in tumor cells, while doxorubicin did not. While free ellagic acid had no effect on the granulocyte-colony stimulating factor and regulated on activation normal T cell expressed and secreted protein, the encapsulated metalla-prism 10 stimulated granulocyte-colony stimulating factor and reduced regulated on activation normal T cell expressed and secreted protein expression in the RAW264.7 macrophage line. Our results show that ellagic acid encapsulated in metalla-prisms inhibited cancer cells via the modulation of mRNA induction and protein expression levels of the granulocyte-colony stimulating factor and regulated on activation normal T cell expressed and secreted protein in macrophages. Keywords: metalla-prism, antioxidant, tumoricidal assay, G-CSF, Rantes